Analysis of Cassava Peel Paste as An Electrolyte of Electrical Energy Source - Supriyanto, Amir (Journal of Technomaterial Physics, 2019)
The electrical characteristics of cassava peel can be detected by using a pair of electrodes, Cu and Zn. Measurement of electrical characteristics is done when the cassava peel is given a 5 watt LED load and when the load is removed. Cassava peel are used in two different ways: fermented and non-fermented. The electrolyte cell used consisted of 20 cells, assembled in three different types: 20 series, 10 series with 2 parallel, and 5 series with 4 parallel. The volume of each cell's paste is 200 ml. The measurement results show that the 20 series circuit produces the greatest electrical voltage, but the electric current is small and the resistance is large. While the series with 20 cells and 5 series with 4 parallel obtained maximum power. The cassava peel which were fermented for 72 hours can increase the electrical power generated from the three types of circuits.